A study on the reduction of hexavalent chromium in aqueous solutions by vinasse - Altundoğan, Hamdi Soner; Özer, Ahmet; Tümen, Fikret (My University, 2004)
Hexavalent chromium introduced to the water ecosystem is an important issue due to the toxic effect it poses. The first step of conventional treatment of wastewaters containing hexavalent chromium is its reduction to chromium (III) which is less toxic. The use of industrial waste material for the reduction of chromium (VI) may be a new cost-effective alternative. In this study, Cr(VI) reduction characteristics of vinasse which is a waste material of alcohol production from sugar beet molasses was investigated. The parameters of pH, temperature, concentrations of initial Cr(VI) and vinasse on the reduction of Cr(VI) were examined as a function of time by applying batch tests. Cr(VI) was almost completely reduced within about 270 min in the concentrations of Cr(VI) and vinasse of 80 mg l-1 and 200 ml l-1, respectively, at pH 3.0 and 25°C. The results showed that reduction time can be shortened by increasing acidity and vinasse concentration or decreasing Cr(VI) initial concentration. Cr(VI) reduction process was found be obey first order kinetic model of homogenous phase reactions. The temperature was found to have a positive effect on the reduction process and the activation energy of process was calculated as 46.07 kJ mol-1. Although the detoxification of wastewaters containing Cr(VI) via reducing it to Cr(III) by using vinasse seems to be costeffective, the resulting effluent to be produced necessitates a further treatment to reduce organic pollution.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hexavalent chromium; Reduction; Detoxification; Vinasse; Distillery waste